Only One Pair of Eyes - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes how too much or too little light can be harmful to the eyes. Describes solutions for home lighting intended to soothe one's eyes. Encourages determining a gentle color scheme for one's home and using paint products that provide a balanced amount of light reflection. Includes small illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Eyestrain; Eye--Protection